Le gouvernement chinois peut-il réorienter le régime d’accumulation ? Une analyse au prisme des transformations du rapport salarial - Clément Séhier (Revue de la Régulation)
The Chinese regime of accumulation based on exports and investments seems to be reaching its limits. The Chinese leaders are convinced of the need to rebalance the economy by prompting domestic demand. The assertion of the social role of the State since the 2000s is part of this objective and has two aims: to reduce the contradictions of the current accumulation regime and to contain the risks of social instability by limiting the social risks stemming from the rise of market mechanisms. However, the institutionalisation of social policies formulated by central authorities is hampered by the resistance of local governments and capitalists. Consequently, inequalities persist, labour conflicts intensify, and the rebalancing of the accumulation regime is curtailed. The CCP is therefore in a paradoxical situation. As it officially stands for the interests of the population, it must promote a better integration of workers. However, by denying them the right to organise to defend their own rights, it deprives itself of a social force capable of putting pressure for the implementation of more protective rules within enterprises. Based on the example of collective bargaining experiences in the coastal provinces, we argue that better integration of workers’ interests into the industrial relations system would strengthen the obligations of employers and would support more broadly the economic and social objectives put forward by the central government.